A new MEIOB mutation is a recurrent cause for azoospermia and testicular meiotic arrest. Issue 4 (6th March 2019) - Gershoni, Moran; Hauser, Ron; Barda, Shimi; Lehavi, Ofer; Arama, Eli; Pietrokovski, Shmuel; Kleiman, Sandra E
Abstract: STUDY QUESTION: Are there genetic variants that can be used for the clinical evaluation of azoospermic men? SUMMARY ANSWER: A novel homozygous frame-shift mutation in the MEIOB gene was identified in three azoospermic patients from two different families. WHAT IS KNOWN ALREADY: Up to 1% of all men have complete absence of sperm in the semen, a condition known as azoospermia. There are very few tools for determining the etiology of azoospermia and the likelihood of sperm cells in the testis. The MEIOB gene codes for a single-strand DNA binding protein required for DNA double-strand breaks repair during meiosis. MEIOB appears to be exclusively expressed in human and mouse testis, and MeioB knockout mice are azoospermic due to meiotic arrest. STUDY DESIGN, SIZE, DURATION: Two brothers with non-obstructive azoospermia (NOA) underwent whole-exome sequencing followed by comprehensive bioinformatics analyses. Candidate variations were further screened in infertile and fertile men, as well as in public and local reference databases. PARTICIPANTS/MATERIALS, SETTING, METHODS: This study included 159 infertile and 77 fertile men. The exomes of two Arab men were completely sequenced. In addition, 213 other men of the same Arab ethnicity (136 infertile and 77 fertile men) underwent restriction fragment length polymorphism (RFLP) screening, as did 21 NOA men, of other ethnicities, with testicular impairment of spermatocyte arrest. All of the infertile men underwent Y-chromosome microdeletion and CFTR gene mutation assessments. Comprehensive bioinformatics analyses were designed to uncover candidate mutations associated with azoospermia. MAIN RESULTS AND THE ROLE OF CHANCE: A novel homozygous frame-shift mutation in the MEIOB gene was identified in two brothers of Arab ethnicity. This frame-shift is predicted to result in a truncated MEIOB protein, which lacks the conserved C-terminal DNA binding domain. RFLP screening of the mutation in 157 infertile men, including 112 NOA patients of Arab ethnicity, identified an additional unrelated NOA patient with the same homozygous mutation and a similar testicular impairment. This mutation was not found in available public databases ( n > 160 000), nor in the 77 proven fertile men, nor in our database of local Israeli population variations derived from exome and genome sequencing data ( n = 500). LIMITATIONS, REASONS FOR CAUTION: We have thus far screened for only two specific MEIOB probable pathogenic mutations in a relatively small local cohort. Therefore, the relative incidence of MEIOB mutations in azoospermia should be further assessed in larger and diverse cohorts in order to determine the efficiency of MEIOB sequence screening for clinical evaluations. WIDER IMPLICATIONS OF THE FINDINGS: The relatively high incidence of likely NOA-causing mutations in MEIOB that was found in our cohort supports the idea that a complete screening of this gene might be beneficial for clinical evaluation of NOA patients. STUDY FUNDING/COMPETING INTEREST(S): This research was supported in part by a grant to EA from the European Research Council under the European Union's Seventh Framework Programme (FP/2007–2013)/ERC grant agreement (616088). There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.